Simulation of TDR circuit for the analysis of wave propagation in XLPE cable model - Rahim N.H.; Sutan Chairul I.; Ab Ghani S.; Ahmad Khiar M.S.; Abas N.; Md Thayoob Y.H. (2023)
Wave propagation characteristic of single phase medium voltage MV cross-linked-polyethylene (XLPE) cable is determined by using Time Domain Reflectometry (TDR). It involves sending electrical pulse along a cable by using an oscilloscope to observe the reflected pulses. By using electrical circuit analysis and transmission line theory, the relationship between the actual and the reflected pulses from the test cable to the reflected pulses measured from an oscilloscope can be obtained. In actual field, test cable is usually lossy cable. By using the high frequency XLPE cable model, the distributed parameters which consist of R, resistance per-unit length (mu/m), L, inductance per-unit length (H/m), C, capacitance per-unit length (F/m) and G, conductance per-unit length (S/m) are represented and applied in the TDR PSpice circuit simulation. Therefore by using simulation of TDR in PSpice circuit, it delivered the wave propagation characteristic which is attenuation. This paper as a reference guides to study how wave propagate in TDR measurement system and from the analysis and results of TDR simulation, the attenuation from XLPE cable model can be obtained. 2012 IEEE.